2020
DOI: 10.21093/ijeltal.v5i1.627
|View full text |Cite
|
Sign up to set email alerts
|

The Violation of Maxims in Indonesian Speech of Mental Retardation Child

Abstract: This article aims to describe the violations of the maxims in the Indonesian speech of mentally retarded children. This study used a descriptive qualitative method. The data source of this study is one mild mental retardation child. The data of this research are words, phrases, and sentences that contain violations of the maxims in the principle of cooperation. Data collection techniques in this study were observation, stimulating, recording, and field recording. Data collection procedures in this study includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…In contrast to study findings [11], the maxim violation of children with intellectual disabilities is generally the maxim of relevance. This shows that the violation of the maxim of relevance in early childhood is normally the minimum violation.…”
Section: Violation Of the Maxim Of Mannermentioning
confidence: 62%
See 2 more Smart Citations
“…In contrast to study findings [11], the maxim violation of children with intellectual disabilities is generally the maxim of relevance. This shows that the violation of the maxim of relevance in early childhood is normally the minimum violation.…”
Section: Violation Of the Maxim Of Mannermentioning
confidence: 62%
“…Violations of maxims occur when the speaker does not know the truth and only understands the surface meaning of the words. The speaker intentionally conveys information that is ineffective, irrelevant or with a meaning that the speaker does not think is wrong [11].…”
Section: Literature Review 21 Grice's Cooperative Maximmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the finding of this current research is also contrasted with the study by Satria Raharja & Rosyidha (2019) that there were four violations of maxims from 29 conversations by Dodit Mulyanto in Stand Up Comedy Indonesia season 4 on Kompas TV and the most dominant was maxim of relation because the actor spoke too digress resulting in unwanted messages with topic and also suddenly changed, but the purpose was just for humour. Then, the current study is also contrasted by the study by Retnosari et al (2020) showed that the maxim of relation was most violated by the Indonesian children with mental retardation because they were not interested to certain topic so they often changed the topic of speech. The finding among this current research against the prior study is different because of the number of the violated maxims in each film is depended on the context or certain situation faced by the speakers.…”
Section: Discussionmentioning
confidence: 75%
“…2, September 2022 Doi: http://dx.doi.org/10.30651/tell.v10i2.14389 Several previous studies also have presented the result of the violated maxim in various objects. Retnosari, et al (2020) showed in their study that the maxim of relation was most violated by the Indonesian children with mental retardation because they were not interested to certain topic so they often changed the topic of speech. Actually, the children also violated quality, quantity, and manner maxims, but these maxims were not dominant.…”
Section: Introductionmentioning
confidence: 99%